REVISITING BEBBINGTON'S CLASSIC RENDERING OF MODERN EVANGELICALISM AT POINTS OF NEW DEPARTURE. - Dochuk, Darren (Fides et historia, 2015)
The article examines the depiction of modern evangelicalism by British historian David W. Bebbington in his book "Evangelicalism in Modern Britain." It analyzes several theological characteristics stressed by Bebbington in his quadrilateral definition of evangelicalism. It describes Bebbington's observations on 20th-century British religion. The article also cites the Lausanne Covenant as a relevant summation of late-20th-century evangelical thought.